Comunidades de leveduras associadas a abelhas sem ferrão na região de Mata Seca em Minas Gerais - Juliana de Freitas Teixeira (2019)
The dry forest ecotone, a transition region between cerrado and caatinga, shelters a great biodiversity native stingless bee species. These bees are closely related to several species of yeast, mainly species of the genera Starmerella and Zygosaccharomyces. In the present study, the yeast communities associated with two species of native stingless bees, Tetragonisca angustula (jataí) and Scaptotrigona cfr. bipunctata (tubuna), and the specie Apis mellifera were studied in a dry forest area. Three collections were carried out in a dry forest preservation area (Janaúba, Minas Gerais), during the rainy season, at the beginning of the dry season during the flowering period, and at the peak of the dry season. Samples of immature honey, mature honey, pollen and adult individuals were collected in three nests of each species of bee. During the flowering period, samples of flowers of Myracrodruon urundeuva (Aroeira) were collected for being the main source of nectar and pollen for bees in the region. The samples were processed and plated on agar malt extract – yeast extract (YM). Eighty-six yeast isolates were obtained from the samples collected from nests of T. angustula, 184 isolates from the samples of Scaptotrigona, 78 isolates from the samples of A. mellifera and 33 isolates from the flower samples of Aroeira, totaling 381 yeast isolates. Fifty-three yeast species were obtained, including new species. The most frequent species associated with T. angustula was Starmerella etchellsii; Candida parapsilosis was the most frequent associated with A. mellifera. The possible new species Zygosaccharomyces sp.1, next to Z. mellis, was the most frequent species associated with S. cfr. bipunctata. The yeasts of the genus Starmerella were isolated in high numbers, distributed among the substrates and among the three species of bees, indicating endemism. The studied yeast communities present a high number of exclusive species, indicating segregation in the forage sites. The identification of yeast species associated with these insects contribute to the elucidation of the microbioma of native stingless bees and its biodiversity.